Analisis Hukum Tentang Kepentingan Umum Menurut Pasal 310 Ayat (3) KUHP di Indonesia sebagai Alasan Penghapusan Pidana dalam Kegiatan Pers - Aditya Pranata Kaban; M. Hamdan; Budiman Ginting; Mahmud Mulyadi (Mahadi: Indonesia Journal of Law, 2022)
The public interest is the foundation of any norms and rules of law in force in the Republic of Indonesia. It’s because the public interest is most important than others, such as the interests of the state, the interest of a group, and the interests of the individual, after that the public interest is the reason for removing the offense if it can be proved that the punishable act was done in the public interests, in accordance with Article 310 Paragraph (3) of the Criminal Code. As we all know the activities of the Press often cause problems where the press is considered a crime to make " the public interest" an excuse for his actions, regardless of whether the source of the news is true or not. In press activities, other legislation that serves as the founding members of the press to make an article is the Law of the Republic of Indonesia Number. 40 of 1999 on the Press, which regulates the press freedom (sometimes called freedom of the press). Those two things make the press feel that the offense should be resolved by way of press releases, and no longer use the Code as a legal basis. In other words, the Press Act serves as Lex specialis of the Code of Penal Code (Code) in the case of defamation, detraction, and mockery, as well as to resolve disputes with other press.